Phylogenetic and morphological studies in Xylodon (Hymenochaetales, Basidiomycota) with the addition of four new species - Janett Riebesehl; Eugene Yurchenko; Karen K. Nakasone; Ewald Langer (MycoKeys, 2019)
Xylodon (Hymenochaetales, Basidiomycota) is the largest segregate genus of Hyphodontia s.l. Based on molecular and morphological data, 77 species are accepted in Xylodon to date. Phylogenetic analyses of ITS and 28S sequences, including 38 new ITS and 20 28S sequences of Xylodon species, revealed four species new to science. The new taxa X. exilis, X. filicinus, X. follis and X. pseudolanatus from Taiwan, Nepal, Réunion, Belize, and USA are described and illustrated. In addition, species concepts for Odontia vesiculosa from New Zealand and Xylodon lanatus from U.S.A. are revised and the new name X. vesiculosus is proposed. Phylogenetic analyses of the ITS region placed X. spathulatus, X. bubalinus and X. chinensis in a strongly supported clade and demonstrated that they are conspecific. Palifer and Odontiopsis are synonymised under Xylodon based on morphological and sequence data. The following new combinations are proposed: X. erikssonii, X. gamundiae, X. hjortstamii, X. hyphodontinus, X. septocystidiatus and X. verecundus. Line drawings of X. cystidiatus, X. hyphodontinus, X. lanatus and X. vesiculosus, as well as photographs of X. raduloides basidiomata, are provided. A key to X. lanatus and similar species is presented.